Relationship Marketing Orientation and Customer Loyalty in Selected Quick-Service Restaurants in Benin City, Nigeria - Agbonifoh, Christopher Ihionkhan; Ahmadu, Aminu; Okodugha, Nathaniel (NIU Journal of Management Sciences, 2026)
This study explored the influence of relationship marketing orientation on customer loyalty in selected fast-food outlets in Benin City. The research focused on assessing the effect of trust on customer loyalty, examining how communication relates to loyalty, determining the role of commitment in fostering loyalty, and evaluating whether conflict handling contributes to loyalty among fast-food customers in the city. The study population comprised customers of various fast-food outlets, from which a sample of 385 respondents was drawn. All administered questionnaires were retrieved, properly completed, and deemed suitable for analysis. Correlation and multiple regression techniques were employed to determine the significance of the relationships among the variables, with hypotheses tested at the 5% significance level using SPSS. Findings revealed that trust has a positive and significant effect on customer loyalty. Communication also showed a strong and significant association with loyalty. Similarly, commitment demonstrated a positive and significant relationship with customer loyalty. Lastly, conflict handling was found to significantly and positively influence customer loyalty. Based on these outcomes, the study recommended that fast-food outlets in Benin City strengthen transparency in their operations; ensuring customers remain well-informed and confident in the products and services offered. Maintaining consistency in fulfilling promises particularly regarding service quality, product standards, and safety was identified as essential. Keywords: Customer loyalty, fast food, outlets, service quality, relationship marketing.